Application of thresholding technique in determining ratio of blood cells for Leukemia detection - Aimi Salihah, Abdul Nasir; Mustafa, N.; Nashrul Fazli, Mohd Nasir (Universiti Malaysia Perlis, 2009)
Organized by School of Mechatronic Engineering (UniMAP) & co-organized by The Institution of Engineering Malaysia (IEM), 11th - 13th October 2009 at Batu Feringhi, Penang, Malaysia.